2020
DOI: 10.1021/acs.jpclett.0c01416
|View full text |Cite|
|
Sign up to set email alerts
|

Single-Atom Pt+ Derived from the Laser Dissociation of a Platinum Cluster: Insights into Nonoxidative Alkane Conversion

Abstract: The Pt:SC2H4Ph clusters were synthesized via a modified approach in our previous work. 1 Typically, 0.1 mmol H2PtCl6 and 0.1 mmol phenylethanethiol were added to a 15 mL THF solution. After stirring for 20 min, an aqueous solution of NaBH4 (1.5 mmol) was added. Then, (ratio of thiol/Pt: 1/1) was added, and some black precipitates were immediately formed. Then the precipitates were thoroughly washed with methanol and extracted with CH2Cl2 to give Pt clusters, which are characterized by HR-MS analyses. Generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In Figure 1 a schematic representation of the main steps in PDH reaction is shown, which can be summarized in four steps (2), namely C−H activation of propane molecules, cracking, desorption of propylene and deep dehydrogenation of propylene, which are regulated by the effects of promoters and supports on the adsorption of the propyl intermediate [2]. Theoretical and experimental studies have demonstrated that Pt + cations promote the propane dehydrogenation to give the corresponding [Pt + propylene] + and [Pt + propyne] + [13]. Moreover, Pt-Pt ensembles seem to be responsible for the propylene deep dehydrogenation and hydrogenolysis, so the insolation of Pt atoms could be an effective strategy to inhibit the side reactions [14].…”
Section: The Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure 1 a schematic representation of the main steps in PDH reaction is shown, which can be summarized in four steps (2), namely C−H activation of propane molecules, cracking, desorption of propylene and deep dehydrogenation of propylene, which are regulated by the effects of promoters and supports on the adsorption of the propyl intermediate [2]. Theoretical and experimental studies have demonstrated that Pt + cations promote the propane dehydrogenation to give the corresponding [Pt + propylene] + and [Pt + propyne] + [13]. Moreover, Pt-Pt ensembles seem to be responsible for the propylene deep dehydrogenation and hydrogenolysis, so the insolation of Pt atoms could be an effective strategy to inhibit the side reactions [14].…”
Section: The Reactionmentioning
confidence: 99%
“…The addition of H 2 seems to help maintain the surface states of the active metals in the Pt-Sn/SiO 2 catalysts under the reaction conditions. [13]. Moreover, Pt-Pt ensembles seem to be responsible for the propylene deep dehydrogenation and hydrogenolysis, so the insolation of Pt atoms could be an effective strategy to inhibit the side reactions [14].…”
Section: The Reactionmentioning
confidence: 99%
“…2 However, currently, there are no known non-precious-metal catalysts that offer the same activity and durability as PtNP/CB. The following facts have recently been clarified for Pt nanoclusters 3,4 with a particle size of ~1 nm which are smaller than Pt NPs; 1) ~1-nm Pt NCs have higher mass activity than Pt NPs 5−9 and 2) the mass activity of ~1-nm Pt NCs varies dramatically depending on the number of constituent atoms. 5−9 Accordingly, if highly active ~1-nm Pt NCs can be synthesized with a narrow distribution in the number of the constituent atoms 9,10 and can then be supported on CB without aggregation, it might be possible to create a highly active ORR catalyst, leading to the cost reduction of PEFCs.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the atomistic details of the photoreactions of Au25 , we performed PD-MS on a homemade system of a Thermo Exactive plus EMR HRMS instrument (Figure S1) using different lasers (e.g., 455, 193, and 154 nm). , Note that the effect of the P25 support was omitted here, as the absorption of P25 occurs at <400 nm. Figure S5 showed that a single MS peak at 4252.58 Da was ascribed to the intact Au25 cluster.…”
mentioning
confidence: 99%